De la loi de la gravitation universelle à MICROSCOPE - Rodrigues, Manuel (Comptes Rendus. Mécanique)
Since Galileo, the universality of the free fall of bodies has questioned physicists: the fall in the vacuum is independent of mass and composition. With the theory of general relativity, Enstein revolutionized the understanding of gravitation. The principle of Equivalence is then posed by Einstein as the founding principle of general relativity with the first consequence: the universality of free fall. This principle, tested more and more accurately since Galileo, has just taken a new step thanks to the MICROSCOPE space mission, which has improved the precision of the test by two orders of magnitude to $2.7× 10^{-15}$.